Performance characteristics of para swimmers: How effective is the swimming classification system? - Burkett, B.; Payton, C.; van de Vliet, P.; Jarvis, H.; Daly, D.; Mehrkuehler, C.; Kilian, M.; Hogarth, L. (Physical Medicine & Rehabilitation Clinics of North America, 2018)
Swimming is one of the inaugural sports within the Olympic and Paralympic Games, the key difference between the Olympic and Paralympic games being the classification system. The aim of this study was to investigate how effective the current classification system creates clearly differentiated Paralympic competition classes, based on performance time for all swimming strokes and events. Based on the performance characteristics of swimmers within the current classification system, the relationship between impairment and swimming performance is inconsistent, potentially disadvantaging some athletes. Appropriate sports medicine tests are required for the development of an evidence-based swimming classification system.